Perancangan Katalog Method Card dan Strategi Pelatihan Karyawan di PT X Indonesia - Mariani Mariani (Jurnal Titra, 2020)
PT X is a company engaged in manufacturing and is a company producing circuit breakers. PT X is a controlled international subsidiary based in Germany. The Process Optimization (PO) department wants to gather knowledge owned by all departments in PT X. This research aims to design a card method to be a catalog and develop training strategies for employees. Card method is a method card that contains an overview of department knowledge material used for inventory. The card method was previously used by a German company and given to PT X Indonesia, but there are a number of methods that cannot be used. The training catalog is a training supporting catalog that can be accessed by all employees at PT X Indonesia in the form of printed books. Preparation of training strategies with regard to training indicators that influence the methods, number of participants, media, facilities, places, trainers, and training evaluation tools. The results of the evaluation carried out that the majority of PT X departments use the on the job training method with coaching techniques. For the off the job training method, PT X uses lecture or lecture techniques to support discussion and question and answer.